The Shortest (Four‐Step) Total Synthesis of the Eight‐Membered Cyclic Ether (rac)‐ and (–)‐cis‐Lauthisan. Issue 28 (22nd August 2013) - Hernández‐Torres, Gloria; Mateo, Julio; Urbano, Antonio; Carreño, M. Carmen
Abstract: Access to the eight‐membered cyclic ether ( rac )‐ and (–)‐ cis ‐lauthisan was achieved in two complementary ways in only four steps for the longest linear sequence by starting from commercially available materials. The sequence features a cis ‐stereoselective reductive cyclization as the key step. Abstract : Acetylide opening of two epoxides followed by the Rh‐catalyzed 1, 4‐addition of the resulting homopropargylic carbinols to the corresponding enones allows the rapid construction of the carbon skeleton of ( rac )‐ and (–)‐ cis ‐lauthisan, which are synthesized after triple‐bond reduction and cis ‐stereoselective reductive cyclization of the two regioisomeric hydroxy ketones formed.